Analysis of the Efficacy and Safety of Coronary Catheterization through Distal Transradial Access: A Single-Center Data - Huanhuan Wang; Dan Liu; Jidong Guo; Nuerbahati Heisha; Lei Wang; Qiang Zhang; Yihui Han; Xiping Wang; Bo Zhang; Jinqing Yuan; Lijian Gao (Hindawi-Wiley, 2023)
Background and Aims. The distal transradial access (dTRA) is a new puncture site for coronary catheterization. We sought to evaluate the feasibility, safety, and complication rates of using the dTRA for cardiac catheterization in Chinese patients. Methods. A total of 263 consecutive patients who underwent catheterization through the dTRA were enrolled. The primary endpoint of the study was the rate of conversion to another access site due to the impossibility of successful artery puncture or intubation. Secondary safety endpoints were the rates of bleeding-related complications and nerve disorders. Results. Among 263 patients, the puncture success rate was 96.2% (253/263). Eleven patients were successfully punctured, but the guide wire was difficult to advance. One patient had intubation failure, and the success rate of intubation was 91.6% (241/263). Two hundred thirty-three patients underwent puncture via the right dTRA, 5 patients underwent puncture via the left dTRA, and 3 patients underwent puncture via the bilateral dTRA. A total of 158 (65.6%) patients underwent coronary angiography, and 83 (34.4%) patients underwent percutaneous coronary intervention. After the procedure, only 2 (0.8%) patients had mild bleeding at the puncture site, 2 (0.8%) had a forearm hematoma, and no patient had a nerve disorder. Conclusions. DTRA has a low incidence of complications, making it a safe and effective technique for cardiac catheterization.